Meta-analysis of the impact of SPINK1 p.N34S gene variation in Caucasic patients with chronic pancreatitis. An update. Issue 8 (August 2017) - Di Leo, Milena; Bianco, Margherita; Zuppardo, Raffaella Alessia; Guslandi, Mario; Calabrese, Federica; Mannucci, Alessandro; Neri, Tauro Maria; Testoni, Pier Alberto; Leandro, Gioacchino; Cavestro, Giulia Martina
Abstract: Background: SPINK1 p.N34S gene variation is one of the endogenous factors which seem to be associated with chronic pancreatitis (CP). However, in literature there is no clear agreement regarding its contribution in different ethnicity and CP etiologies. Aim: To investigate the role of SPINK1 p.N34S gene variation in CP patients with European origin by means of meta-analysis. Methods: Literature search was conducted and case–control studies evaluating Caucasian population, published between May 2007 and May 2015, were included. We also included Caucasian selected studies analyzed in previous meta-analysis. We carried out meta-analysis including all selected studies. After that, we performed two additional meta-analyses considering the incidence of SPINK1 p.N34S gene variation in alcoholic or in idiopathic CP patients vs control group. Results: Twenty-five studies were included and the total number of subjects was 8800 (2981 cases and 5819 controls). The presence of p.N34S variation increased nine times the overall CP risk in population of European origin [OR 9.695 (CI 95% 7.931–11.851)]. Also, the contribution of SPINK1 in idiopathic pancreatitis [OR 13.640 (CI 95% 8.858–21.002)] was found to be higher than in alcoholic CP [5.283 (CI 95% 3.449–8.092)]. Conclusion: The association between SPINK1 p.N34S gene variation and CP is confirmed. Also, we confirmed that the idiopathic etiology needs a better definition by means of genetic analysis.